Challenges for citizenship and the fundamental rights system in the digital age - Arce Jiménez, Carlos (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
Citizenship, as a legal and political instrument for the ownership and the exercise of Fundamental Rights, faces serious challenges in the context of the digital era and the global expansion of new technologies. These challenges can be named as systemic as they structurally question the concept of citizenship, both in its subjective and objective dimensions and in the legal tools that it requires for its development. This article also analyses the particular obstacles that the digitization and new technologies represent for Fundamental Rights, key in the liberal perspective of citizenship and for the principle of material equality, as well as alternative proposals from legal and political sciences.